An Analysis of Modifiers in Noun Phrase Structures with Nominalized Verb Heads between Vietnamese and English - Thuy, Vu Thanh; Ngoc, Nguyen Thi Thanh (VNU Journal of Science: Education Research; Vol 42 No 2DO - 10.25073/2588-1159/vnuer.5418, 2026)
The article investigates the pre-modifiers and post-modifiers of three-part noun phrase structures of which the heads are nominalized verbs in Vietnamese and English. 600 Vietnamese and English noun phrase structures from various literary works are used for analysis. The results revealed not only the most and the least popular pre-modifier and post-modifier in the noun phrase structure but also the combination of these modifiers in both languages. The analysis of three-part noun phrase structures enables language users to identify the structure, the components, the word classes easily and to determine the distinctive features of noun phrase structures successfully in both languages. This article plays a theoretical and practical role in Vietnamese and English language research. The findings not only strengthen the theories and suggest future research directions on word classes in languages but also are the scientific basis for recommendations for teaching and learning Vietnamese and English.